Case report: Epiglottitis in the setting of COVID-19. (2021) - Smith, Connor; Mobarakai, Olivia; Sahra, Syeda; Twito, Joshua; Mobarakai, Neville
Abstract: Epiglottitis is an uncommon, potentially fatal infection of the epiglottis that can lead to complete upper airway obstruction. Isolated pathogens are usually nasopharyngeal bacteria, most commonly Haemophilus influenzae type b (Hib). While the incidence of epiglottitis has diminished significantly over the years due to widespread vaccination against Hib, the proportion of epiglottitis caused by other pathogens has increased. In this report, we introduce an unseen presentation of acute epiglottitis associated with severe acute respiratory distress syndrome–coronavirus2 (SARS-CoV-2), who presented to the emergency department with throat pain and odynophagia that quickly resulted in respiratory distress. Clinicians should be aware of airway edema's concomitant presence in patients with acute epiglottitis and COVID-19 and maintain a low threshold for intubation. The rapidly progressive nature of COVID-19 and its complications may preclude intubation later on in the patient's clinical course, potentially necessitating an emergent surgical airway.